Inka Unku: Imperial or provincial? State-local relations - Jacqueline Correa-Lau; Carolina Agüero; Jeffrey Splitstoser; Ester Echenique; Tracy Martens; Calogero M. Santoro (PLoS ONE, 2023)
Standardized Inka tunics, or unku, were created under the auspices of the state as symbolic expressions of its expansionist power. To ensure these textiles acquired the status of effective insignias of power and territorial control, the Inka established and imposed technical and stylistic canons for their production (techne) by means of highly-skilled state weavers. In the provinces, social groups that came under imperial rule, local expert weaving agents adopted the conventions of the state and included meaningful symbolic elements of the idiosyncrasies, traditions, and experiential knowledge of the local community (metis). We therefore propose that this was not a unidirectional process and that the Caleta Vitor Inka unku (hereon referred to as the CV unku), presented here, reflects a syncretism promoted by local weavers. In terms of methods, we have developed a decoding tool for the unku, with the aim of distinguishing state from local hallmarks, thereby revealing the syncretic complexity of these iconic tunics. This methodological tool is based on a series of standard analytical parameters and attributes linked to morphological, technological, and stylistic features, which we applied to the CV unku. Unlike others, this unku does come from a looted tomb but was scientifically excavated in a cemetery located in the Caleta Vitor Bay in northern Chile. By deconstructing the CV unku we determined the steps in the chaîne opératoire at which local technical and stylistic elements were incorporated, thus affecting or transforming, in part, its emblematic imperial imagery. This study also marks a step forward in our understanding of a syncretic landscape that combines the state worldview and organized production system (imperial Inka) with craft-production practices that were rooted in provincial and local communities (provincial Inka).